Ergonomical contributions to flight simulators design in virtual reality immersive environment (DAPesquisa, 2018)
This work approaches the developments in research to flight simulators in immersive virtual reality‘s design. Focused in the design field, the research has received substantial resources from agencies of research‘s foment, aiming the overcoming of ergonom- ical deficiencies verified in existing flight simulators, especially in those to military and acrobatics airplanes.